Metodologi Imam Al-Bukhari dalam Menentukan Cacat sebuah Hadis pada Kitab At-Tarikh Al-Kabir Jilid II - Misbah Binasdevi; Armizi Armizi (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2020)
Hadith is the biggest main basis for Islam which is used as a basic guide in carrying out life in the world after the Qur'an. The hadith itself is all that is conveyed by the Prophet Muhammad, be it moral or physical. However, not all of the hadiths come from the Prophet, there are also false hadiths but still called hadiths because their form resembles hadith. the hadith was compiled by the narrators of the hadith whether it was believed or not. The collection of this hadith makes the occurrence of authentic hadiths that are believed to be authentic and are not valid which authenticity must be re-examined. Imam al-Bukhari is one of the scholars who gave an idea of ​​the methodology of determining the flaw of a hadith which he wrote in his book entitled At-Tarikh Al-Kabir Volume II